Tagore and Gandhi argue - Tagore, Rabindranath, 1861-1941 (SAMP early 20th-century Indian books project ;, 1945)
Interchange of political and social views between Rabindranath Tagore, 1861-1941, Bengali and English author and Mahatma Gandhi, 1869-1948, statesman.